PENGENDALIAN KUALITAS PRODUK TEH HIJAU MENGGUNAKAN PENDEKATAN SIX SIGMA - Heru Prastiyo; Firman Ardiansyah Ekoanindiyo (Jurnal Ilmiah Dinamika Teknik, 2014)
PT "X" is a company that processes into a tea leaf green tea which is then resold to other tea companies such as: Sosro, Mount Agung, Indotirta. In PT "X", performed quality control is still less than the maximum. Which will happen eventually if often can be detrimental to the company. To prevent greater loss, then the company needs to think of an effective way so that corrective action can be carried out before its too late. The company must monitor continuously so the products have export quality. Methods of Six Sigma is one of the integral method in quality improvement. This method proved to be effective to improve and enhance the quality of products and processes, and thus the number of defects detrimental to the company can be minimized and eventually expected profit of the company will increase as well. The calculation result obtained DPMO and sigma value overall process DPMO value of 254.8 means that in a million chance there may be a discrepancy amounting to 254.8 opportunities that will lead to defects. While the amount of production of 5850000 units by 5962 the number of defective units and 4 obtained defect opportunity sigma value of 4.98 which means it needs to attempt to achieve sigma sigma value of 6.00 or achievement of zero defect. Kata Kunci: Pengendalian Kualitas, Metode Six Sigma, Zero Defect